TMS reveals a two-stage priming circuit of gesture-speech integration - Zhao, Wanying (Frontiers in Psychology, 2023)
Naturalistically, multisensory information of gesture and speech is intrinsically integrated to enable coherent comprehension. Such cross-modal semantic integration is temporally misaligned, with the onset of gesture preceding the relevant speech segment. It has been proposed that gestures prime subsequent speech. However, there are unresolved questions regarding the roles and time courses that the two sources of information play in integration. Here, in two experiments, we segmented the gesture-speech integration period into 40-ms time windows (TWs) based on two separately division criteria, while interrupting the activity of the integration node of the left posterior middle temporal gyrus (pMTG) and the left inferior frontal gyrus (IFG) with double-pulse transcranial magnetic stimulation (TMS). In Experiment 1, we created fixed time-advances of gesture over speech and divided the TWs from the onset of speech. In Experiment 2, we differentiated the processing stages of gesture and speech and segmented the TWs in reference to the speech lexical identification point (IP), while speech onset occurred at the gesture semantic discrimination point (DP). The results showed a TW-selective interruption of the pMTG and IFG only in Experiment 2, with the pMTG involved in TW1 (-120~-80 ms of speech IP), TW2 (-80~-40 ms), TW6 (80~120 ms) and TW7 (120~160 ms) and the IFG involved in TW3 (-40~0 ms) and TW6. Meanwhile no significant disruption of gesture-speech integration was reported in Experiment 1. We determined that after the representation of gesture has been established, gesture-speech integration occurs such that speech is first primed in a phonological processing stage before gestures are unified with speech to form a coherent meaning. Our findings provide new insights into multisensory speech and co-speech gesture integration by tracking the causal contributions of the two sources of information.